Sustainable Catalytic Synthesis of 2,5-Diformylfuran from Various Carbohydrates - Kim, Si Ae; Sung, Kihyuk; Jang, June Young; Bang, Sohee; Son, Seung Uk; Jang, Hye Young (Catalysts, 2022)
Versatile homogeneous and heterogeneous catalysts that convert carbohydrates to 2,5-diformylfuran (DFF) are essential for the development of sustainable processes for producing high-value chemicals from biomass-derived carbohydrates. An efficient catalytic system consisting of Br−, disulfide, and dimethylsulfoxide (DMSO) promoted the sustainable and selective synthesis of DFF in modest-to-good yields from various carbohydrates, such as fructose, glucose, mannose, galactose, and sucrose. Heterogeneous catalysts containing Br− also facilitated this reaction with recyclable high yields.
Keywords: 2,5-diformylfuran; biomass; carbohydrates; fructose; glucose